Self Regulated Learning dan Self Efficacy Mahasiswa Tim Debat Bahasa Arab al-Kindy - Nuril Mufidah; Warisma Riski Nuryani (Institut Agama Islam Negeri Curup, 2019)
The skill of speaking Arabic is a demand in the campus world and after graduation as a form of readiness to enter the workforce in the global era. Teaching kalam with the debate method for students besides being able to improve ability also adds courage as a form of self-efficacy. Students with Self-regulated learning can complete lecture obligations properly and can participate in extra debate activities as a means of self-development. This study aims to determine whether there is an influence of self-regulated learning and self-efficacy for adult students in Arabic learning especially debate program. The subject of this study are 7 students who had participated in the National or International Arabic debate competition. The study used a descriptive qualitative research type of case study-retrieval of data through interviews and documentation. The results of this study indicate that 78% of their success is influenced by the existence of self-regulated learning and self-efficacy in the debate. The strategy of learning debate by using native speaker videos that are studied independently by each member. Then each member displays the results of their training day in front of the senior.